Canada’s False Guilty Pleas : Lessons from The Canadian Registry of Wrongful Convictions - Roach, Kent (The Wrongful Conviction Law Review, 2023)
The Canadian Registry of Wrongful Convictions www.wrongfulconviction.ca  .like similar registries in the United States and the United Kingdom, was designed to facilitate research on patterns and trends in wrongful convictions.  As of its launch in February 2023, 15 of 83 remedied wrongful convictions or 17% were the result of guilty pleas by the accused. This is a similar percentage as found in a UK registry and lower than the 27% of guilty plea wrongful convictions found in the US registry. Forty percent of the guilty plea wrongful convictions were entered by women. Most of these involved  the flawed expert testimony of Charles Smith about the cause of baby deaths and the majority of all remedied guilty plea wrongful convictions were for imagined crimes that did not happen.  Almost half (7 of 15) of Canada’s false guilty pleas were taken from racialized people including three Indigenous men, one Black and Indigenous man, another Black man and a Brown man who had recently immigrated from India. Two of the fifteen false guilty pleas were taken from accused persons who had diagnosed mental health and cognitive challenges. With the exclusion of one false guilty plea to a mandatory sentence of life imprisonment and ineligibility for parole for 10 years, the average sentence in the remaining 14 cases was 10 months with evidence of “lop-sided” pleas especially in the cases involving Charles Smith and 2 of the 14 received sentences of time already served.